The Evolving Lexicon of Eco-Activism: Exploring the Connection Between Slang and Eco-Journalism (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the potential of incorporating slang words into eco-journalism as a means to enhance accessibility, audience engagement, and cultural relevance. While acknowledging the risks of misinterpretation and loss of scientific accuracy, the paper proposes a theoretical framework for responsible slang usage, emphasizing audience awareness, contextual relevance, and a balance between informality and accuracy. Through case studies and examples, the article demonstrates how slang can effectively bridge the gap between complex environmental issues and everyday understanding, fostering a more inclusive and impactful environmental movement.